2011
DOI: 10.1007/s10900-011-9359-5
|View full text |Cite
|
Sign up to set email alerts
|

Time and Distance Barriers to Mammography Facilities in the Atlanta Metropolitan Area

Abstract: To a great extent, research on geographic accessibility to mammography facilities has focused on urban-rural differences. Spatial accessibility within urban areas can nonetheless pose a challenge, especially for minorities and low-income urban residents who are more likely to depend on public transportation. To examine spatial and temporal accessibility to mammography facilities in the Atlanta metropolitan area by public and private transportation, we built a multimodal transportation network model including b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 38 publications
1
65
0
1
Order By: Relevance
“…Income inequality, mammography capacity, and the proportion of digital machines were largest for the metropolitan counties. While services may be present in metropolitan counties with high income inequalities as demanded by high income groups, these services may not be accessible to the lowest income groups within that county whose dependence on public transportation may limit access [31]. Household income inequality ratio was the same for rural capacity and zero-capacity counties.…”
Section: Discussionmentioning
confidence: 90%
“…Income inequality, mammography capacity, and the proportion of digital machines were largest for the metropolitan counties. While services may be present in metropolitan counties with high income inequalities as demanded by high income groups, these services may not be accessible to the lowest income groups within that county whose dependence on public transportation may limit access [31]. Household income inequality ratio was the same for rural capacity and zero-capacity counties.…”
Section: Discussionmentioning
confidence: 90%
“…Weinreb et al (2006) found that caregivers, females in particular, who live in communities that lack social capital (i.e., social support, financial resources, safe neighborhoods) tend to utilize fewer community-based health services and may rely extensively on short-term emergency/urgent care services (Weinreb et al 2006). Furthermore, communities characterized by instability and poverty are likely to experience racial disparities in mental health services for youth (Gudiño et al 2009) and lack easily accessible, high quality healthcare (Dai 2010;Guagliardo et al 2004;Lillie-Blanton and Hoffman 2005;Peipins et al 2011).…”
Section: Caregiver Service Utilization and Child Mental Healthmentioning
confidence: 99%
“…Using these networks, we calculated travel times to radiation facilities via public and private vehicle transportation from a population-weighted center of each of the 282 census tracts located within the 2-county area served by the Metropolitan Atlanta Rapid Transit Authority (MARTA). A full description of the construction of the multimodal public transportation models has been published previously (Peipins et al, 2011).…”
Section: Overviewmentioning
confidence: 99%